کتاب و سنت سے متعلق قواعد اصولیہ اور عائشہ رضی اللہ عنہا کی فقہ - Muhammad Mujahid Farid; Hafiz Abdul Rahman Madni (الآفاق اسلامی و تحقیقی مجلہ)
This article examines the Qawāʿid Uṣūliyyah (principles of Islamic jurisprudence) concerning the Qur’an and Sunnah through the jurisprudential contributions of ‘Aishah (RA). As one of the most knowledgeable companions of Prophet Muhammad (PBUH), Aisha (RA) played a pivotal role in interpreting and applying Islamic teachings. Her profound understanding of the Qur’an and Sunnah, coupled with her critical legal reasoning, significantly shaped early Islamic jurisprudence. This study explores her methodological approach, emphasizing the key principles she employed in deriving legal rulings, reconciling apparent contradictions, and contextualizing prophetic traditions. Through an analysis of selected narrations and legal opinions attributed to Aisha (RA), the article highlights her scholarly influence and lasting impact on Islamic legal thought. The findings underscore her authoritative role in Fiqh and demonstrate how her interpretative methods continue to inform contemporary Islamic jurisprudence.